A retrospective study of paediatric oral lesions from Thailand - KITTIPONG DHANUTHAI, MARUT BANRAI, & SOMYOT LIMPANAPUTTAJAK (IAPD and Blackwell, 2007)
Children are a distinct group of the population.They differ from the general population not only because of their small sizes, but also because certain lesions have a predilection for this population group such as Langerhans cell histiocytosis and some types of lymphoma,leukaemia, and haemangioma.